Thy-1 glycoprotein and src-like protein-tyrosine kinase p53/p56lyn are associated in large detergent-resistant complexes in rat basophilic leukemia cells - Dráberová, L; Dráber, P (Proceedings of the National Academy of Sciences of the United States of America, 1993)
Thy-1 is a surface glycoprotein that is attached to the plasma membrane by a glycosyl-phosphatidyl-inositol anchor. Crosslinking of Thy-1 in rat mast cells and basophilic leukemia cells (RBL-2H3) induces cell activation including histamine release and tyrosine phosphorylation of several proteins. Here we show that glycosyl-phosphatidylinositol-linked Thy-1 forms noncovalent complexes with src-related protein-tyrosine kinase p53/p56lyn and other protein-tyrosine kinases and/or their substrates. These complexes are resistant to solubilization by a nonionic detergent, sedimentable at 200,000 x g, and very large ( > 10 MDa) as determined by gel chromatography. Activation of RBL-2H3 cells by crosslinking of the high-affinity IgE receptors resulted in decreased recovery of the complexes. The combined data indicate the existence of large detergent-resistant domains in the surface membrane of mast cells that may play an important role in their activation.
Keywords: fosfodiesterasy; src-Family Kinases; membránové glykoproteiny; Protein-Tyrosine Kinases; gelová chromatografie; tyrosinkinasy; C-terminální Src kinasa; Chromatography, Gel; Tumor Cells, Cultured; protoonkogenní proteiny pp60(c-src); Animals; lyasa fosfatidylinositoldiacylglycerolu; Electrophoresis, Polyacrylamide Gel; skupina kinas odvozených od src-genu; imunoblotting; Antigens, Surface; Immunoblotting; CSK Tyrosine-Protein Kinase; krysa rodu Rattus; Leukemia, Basophilic, Acute; Thy-1 Antigens; monoklonální protilátky; Receptors, IgE; Rats; makromolekulární látky; molekulová hmotnost; Antibodies, Monoclonal; antigeny Thy-1; akutní bazofilní leukemie; receptory IgE; nádorové buňky kultivované; zvířata; Molecular Weight; Proto-Oncogene Proteins pp60(c-src); Phosphatidylinositol Diacylglycerol-Lyase; Phosphoric Diester Hydrolases; Membrane Glycoproteins; elektroforéza v polyakrylamidovém gelu; antigeny povrchové; Macromolecular Substances